Pengukuran Tingkat Pemahaman Masyarakat Desa Gandulan Tentang Pengelolaan Lingkungan Melalui Sosialisasi 4P - Purnama, Vilan; Rifai, Rizal; Ni’mah, Maskurotun; Naila, Siti Aza Nur; Sofyan, Muhammad Abu; Deffani, Eggiyana Dwi; Hilyati, Alfi; Awaliyah, Hana Zahrotul; Oktaviani, Wulan; Adiningrum, Dinda; Nurhidayati, Astri; Khoirullah, Rizqi; Rahman, Rifqi Aulia; Wibowo, Yusuf Adhi (Pakis Journal Institute, 2025)
Good environmental management is one of the key factors in improving the quality of life in society. The 4P socialization program (Penanaman, Perawatan, Pemanfaatan, and Pengelolaan) is an initiative aimed at raising public awareness about environmental conservation by planting, maintaining, utilizing, and managing natural resources sustainably. Planting and maintaining focus on growing vegetables and other plants, while utilization and management emphasize how to make use of and handle household organic and inorganic waste. This activity involved an initial observation, preparation for socialization, and the implementation of the socialization program at the Gandulan Village Hall. Observations showed that Gandulan Hamlet had implemented better environmental management compared to other hamlets. Through this initiative, it is hoped that other hamlets will continue to manage their environment sustainably. The socialization, attended by 22 participants and presented by the DPRKPLH of Temanggung Regency, covered various aspects such as environmental conservation, waste sorting, and composting. The results of a post-test conducted after the socialization showed that the community’s awareness and understanding of environmental management reached 83.3%, which is expected to contribute to the sustainability of the village environment.